Restrukturisasi Psikoterapi Dan Relaksasi Emosi, Otot Untuk Mengurangi Insomnia - Aries Dirgayunita; Benny Prasetiya ((JKG) Jurnal Keperawatan Global, 2019)
Backgound: Difficulty sleeping or insomnia is a complaint about the lack of quality sleep caused by one of; it is difficult to enter sleep, often wake up at night then difficulty to go back to sleep, wake up too early, and sleep badly. Insomnia is not caused by at least one person sleeping, because everyone has a number of hours of sleep on their own. This is a case study of subjects who experience symptoms of insomnia due to stress. Besides subject matter experience, because of academic and family factors. Interventions used are cognitive restructuring and emotional relaxation therapy, muscle. Methods: This study uses a psychological assessment which is an activity to collect subject data using data collection techniques from observation, interviews, and psychological tests. Result: the results of therapy that have been carried out using the interview method conducted directly to the subject, several days after the therapy was carried out experienced significant success. Conclusion: the application of restructuring of psychotherapy and relaxation of emotions, muscles can reduce insomnia